Genetic Ancestry of Hadza and Sandawe Peoples Reveals Ancient Population Structure in Africa. (14th March 2018) - Shriner, Daniel; Tekola-Ayele, Fasil; Adeyemo, Adebowale; Rotimi, Charles N
Abstract: The Hadza and Sandawe populations in present-day Tanzania speak languages containing click sounds and therefore thought to be distantly related to southern African Khoisan languages. We analyzed genome-wide genotype data for individuals sampled from the Hadza and Sandawe populations in the context of a global data set of 3, 528 individuals from 163 ethno-linguistic groups. We found that Hadza and Sandawe individuals share ancestry distinct from and most closely related to Omotic ancestry; share Khoisan ancestry with populations such as ≠Khomani, Karretjie, and Ju/'hoansi in southern Africa; share Niger-Congo ancestry with populations such as Yoruba from Nigeria and Luhya from Kenya, consistent with migration associated with the Bantu Expansion; and share Cushitic ancestry with Somali, multiple Ethiopian populations, the Maasai population in Kenya, and the Nama population in Namibia. We detected evidence for low levels of Arabian, Nilo-Saharan, and Pygmy ancestries in a minority of individuals. Our results indicate that west Eurasian ancestry in eastern Africa is more precisely the Arabian parent of Cushitic ancestry. Relative to the Out-of-Africa migrations, Hadza ancestry emerged early whereas Sandawe ancestry emerged late.